General practitioners and emergency departments (GPED)—efficient models of care: a mixed-methods study protocol. Issue 10 (3rd October 2018) - Morton, Katherine; Voss, Sarah; Adamson, Joy; Baxter, Helen; Bloor, Karen; Brandling, Janet; Cowlishaw, Sean; Doran, Tim; Gibson, Andrew; Gutacker, Nils; Liu, Dan; Purdy, Sarah; et al.
Abstract : Introduction: Pressure continues to grow on emergency departments in the UK and throughout the world, with declining performance and adverse effects on patient outcome, safety and experience. One proposed solution is to locate general practitioners to work in or alongside the emergency department (GPED). Several GPED models have been introduced, however, evidence of effectiveness is weak. This study aims to evaluate the impact of GPED on patient care, the primary care and acute hospital team and the wider urgent care system. Methods and analysis: The study will be divided into three work packages (WPs). WP-A; Mapping and Taxonomy: mapping, description and classification of current models of GPED in all emergency departments in England and interviews with key informants to examine the hypotheses that underpin GPED. WP-B; Quantitative Analysis of National Data: measurement of the effectiveness, costs and consequences of the GPED models identified in WP-A, compared with a no-GPED model, using retrospective analysis of Hospital Episode Statistics Data. WP-C; Case Studies: detailed case studies of different GPED models using a mixture of qualitative and quantitative methods including: non-participant observation of clinical care, semistructured interviews with staff, patients and carers; workforce surveys with emergency department staff and analysis of available local routinely collected hospital data. Prospective case study sites will be identified by completing telephone interviews with sites awarded capital funding by the UK government to implement GPED initiatives. The study has a strong patient and public involvement group that has contributed to study design and materials, and which will be closely involved in data interpretation and dissemination. Ethics and dissemination: The study has been approved by the National Health Service East Midlands—Leicester South Research Ethics Committee: 17/EM/0312. The results of the study will be disseminated through peer-reviewed journals, conferences and a planned programme of knowledge mobilisation. Trial registration number: ISRCTN51780222 .